Priming to protect maize from Fusarium verticillioides and its fumonisin accumulation. (16th July 2018) - Aguado, Ana; Savoie, Jean‐Michel; Chéreau, Sylvain; Ducos, Christine; Aguilar, María; Ferrer, Nathalie; Aguilar, Manuel; Pinson‐Gadais, Laetitia; Richard‐Forget, Florence
Abstract: BACKGROUND: Systemic infection through the seed is one of the routes used by the mycotoxinogenic pathogen Fusarium verticillioides for colonizing maize plants. The prohibition of the use of most chemical fungicides by the EU has promoted research on plant resistance inducers as an effective and sustainable alternative. Induction of a priming state in maize seeds might affect their susceptibility to contamination and accumulation of fumonisins. This state by application of a natural fertilizer called Chamae on maize seeds, was investigated in two varieties to control the colonization by the fungus and the accumulation of fumonisins B1, B2 and B3, germinating seeds, dead plants and yield. RESULTS: After inoculation of F. verticillioides on germinating seeds, the colonization by the fungus and the accumulation of fumonisins were significantly lower in seedlings coming from treated seeds, but a significant number of plants stopped their development by necrosis. In a field trial, the 0.01% (v/v) application dilution showed a lower plant density, although the level of biomass at harvest was not affected. CONCLUSION: The priming state contributed to the control of F. verticillioides development from seed infection and fumonisin accumulation in the early stage of plant growth, without affecting the final crop yield, and could reduce fungicide use and environmental contamination. © 2018 Society of Chemical Industry